A participatory approach to the establishment of a baseline scenario for a reforestation Clean Develop ment Mechanism project (2006)
eng: This paper is part of a two-year study to investigate the feasibility of initiating a Clean Development Mechanism (CDM) project in an indigenous community of Eastern Panamá, Ipetí-Emberá. We use participatory mapping and matrices as well as household surveys to develop a land-use/land-cover baseline scenario and examine the role of local participation in assessing land-use change. In Ipetí, land-use change has not occurred in a linear way over the last decades, and our data unveils socio-economic factors as potential key drivers of change.